2014
DOI: 10.1186/1472-6963-14-214
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of physicians by nurses in primary care: a systematic review and meta-analysis

Abstract: BackgroundIn many countries, substitution of physicians by nurses has become common due to the shortage of physicians and the need for high-quality, affordable care, especially for chronic and multi-morbid patients. We examined the evidence on the clinical effectiveness and care costs of physician-nurse substitution in primary care.MethodsWe systematically searched OVID Medline and Embase, The Cochrane Library and CINAHL, up to August 2012; selected and critically appraised published randomised controlled tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
205
1
11

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(229 citation statements)
references
References 41 publications
12
205
1
11
Order By: Relevance
“…Additionally, the demand for endoscopic procedures in general has increased considerably over the past decades, e.g., owing to the introduction of colorectal screening programs and advanced therapeutic endoscopy ( 15 ). Several studies have shown that some tasks in health care, including endoscopies and colonoscopies, can successfully be shift ed from physicians to nurses (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the demand for endoscopic procedures in general has increased considerably over the past decades, e.g., owing to the introduction of colorectal screening programs and advanced therapeutic endoscopy ( 15 ). Several studies have shown that some tasks in health care, including endoscopies and colonoscopies, can successfully be shift ed from physicians to nurses (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…priporočilom, ki definirajo diagnostično-terapevtske in edukacijske poti obravnave pacientov v ambulanti zdravnika družinske medicine in ki so usklajeni in dogovorjeni med strokovnjaki z različnih ravni zdravstvenega varstva (primarni, sekundarni in terciarni nivo) (Vodopivec Jamšek, 2013). Bistvena elementa pri obravnavi pacientov v RADM sta razdelitev dela med člani tima v skladu s kompetencami posamezne stroke in njihovo medsebojno sodelovanje (Poplas Susič, et al, 2013;Martínez-González, et al, 2014).…”
Section: Slovenian Translation/prevod V Slovenščinounclassified
“…The division of labour among team members in line with the competencies of individual professions and their mutual collaboration (Poplas Susič, et al, 2013;Martínez-González, et al, 2014) are two key elements of patient treatment in FMRCs.…”
mentioning
confidence: 99%
“…The notion of independent medical care by NPs (and PAs) caught the imagination of policy-makers, and the Patient Protection and Affordable Care Act of 2010 (PPACA) announced increased funding for clinics run by NPs. There is, however, lack of cost-effectiveness evidence of substituting nurses for physicians [8,[51][52][53]. Educating NPs may be (much) shorter and cheaper than physicians, but without taking into account their relative incomes and the numbers of patients they see each day (and additional costs of referrals, prescriptions and testing), is it hard to assess the cost-benefit ratio of such Traditionally, private insurers typically use those schedules as a template for their own fees.…”
Section: Countrymentioning
confidence: 99%